2020
DOI: 10.1186/s12955-020-01587-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of oral health-related quality of life in 2–5 year-old children in the South of Iran

Abstract: Background Dental and oral diseases can have negative impacts on children’s quality of life. The aim of this study was to determine the predictors of oral health-related quality of life (OHRQoL) in the children aged 2–5 years old. Materials and methods A total number of 288 children aged between 2 and 5 years were selected and stratified by gender from three community health centres located in the city of Jahrom, south of Fars Province, Iran. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Even though most adults have some gingival inflammation (gingivitis), around 11% of the global adult population has severe progressive periodontal diseases, leading to tooth loss at an early age [2]. According to a recent global burden of disease survey, oral disorders are responsible for 15 million disabilities globally (Figure 1) [2].As perAbbasi-Shavaziand his colleagues, the deciding factors for children's oral health-related quality of life (OHRQoL) involvestrengthening, predisposing, and oral health behaviorand status [3].On the other hand, Zhang and his teammates found that risk predictors responsible for root caries can be categorized based on age, socioeconomic status, and tobacco usage. Moreover, patients with gingival recession, poor oral hygiene, and prior dental caries are more susceptible to developing new root caries [4].…”
Section: Importance Of Oral Hygienementioning
confidence: 99%
“…Even though most adults have some gingival inflammation (gingivitis), around 11% of the global adult population has severe progressive periodontal diseases, leading to tooth loss at an early age [2]. According to a recent global burden of disease survey, oral disorders are responsible for 15 million disabilities globally (Figure 1) [2].As perAbbasi-Shavaziand his colleagues, the deciding factors for children's oral health-related quality of life (OHRQoL) involvestrengthening, predisposing, and oral health behaviorand status [3].On the other hand, Zhang and his teammates found that risk predictors responsible for root caries can be categorized based on age, socioeconomic status, and tobacco usage. Moreover, patients with gingival recession, poor oral hygiene, and prior dental caries are more susceptible to developing new root caries [4].…”
Section: Importance Of Oral Hygienementioning
confidence: 99%